2009
DOI: 10.1200/jco.2009.27.15_suppl.10503
|View full text |Cite
|
Sign up to set email alerts
|

A SARC global collaborative phase II trial of R1507, a recombinant human monoclonal antibody to the insulin-like growth factor-1 receptor (IGF1R) in patients with recurrent or refractory sarcomas

Abstract: 10503 Background: The IGF1 system has been implicated in sarcoma development and inhibition of IGF1R function has been shown to induce clinical responses in select sarcomas. Methods: Objectives included response rate (RR) and progression-free survival (PFS) to R1507 in patients with recurrent or refractory Ewing's (ES, 2 cohorts- primary refractory vs. others) osteo (OS), synovial (SS), rhabdomyosarcoma (RMS), and other sarcomas. Eligibility included recurrent/refractory measurable disease, age ≥ 12 yrs, life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The most notable activity of anti–IGF-1R mAbs was demonstrated in EWS, with reports of complete responses (CRs) or partial responses (PRs) and prolonged stable disease (SD) in phase 1 trials [33] , [39] [41] . These promising results led to a series of phase 2 evaluations in the indication ( Table 4 ).…”
Section: Clinical Experience With Igf-1r Inhibitorsmentioning
confidence: 99%
“…The most notable activity of anti–IGF-1R mAbs was demonstrated in EWS, with reports of complete responses (CRs) or partial responses (PRs) and prolonged stable disease (SD) in phase 1 trials [33] , [39] [41] . These promising results led to a series of phase 2 evaluations in the indication ( Table 4 ).…”
Section: Clinical Experience With Igf-1r Inhibitorsmentioning
confidence: 99%
“…The activity of IGF1R monoclonal antibodies has been confirmed by the early reports of clinical activity in Ewing sarcoma [ 89 91 , 94 ]. However, in RMS patients, despite some responses observed with R1507 [ 92 ], targeting IGF1R alone does not seem the optimal strategy due to the complexity of this pathway and the key role of IGF2 in this pathology. To extend the benefits of these therapeutic approaches there is an urgent need to identify predictive biomarkers to improve patient selection and facilitate the development of rational combination regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Both cases were heavily pretreated metastatic ARMS and both progressed within 6 weeks of starting treatment on figitumumab (a monoclonal antibody against IGF1R) [ 89 ]. More recently, in a preliminary report of the SARC011, a phase II trial in multiple sarcoma types, described 3 objective radiological responses in patients with RMS treated with the anti-IGF1R antibody R1507 [ 92 ]. However, more mature data in Ewing's sarcoma has shown that many responses only lasted for a finite period of time [ 93 , 94 ].…”
Section: Clinical Targeting Of Igf1r In Rms: Evidence and Trendsmentioning
confidence: 99%
“…A second, and more challenging, model occurs when targeted agents show insufficient promise in adult cancers to merit further commercial development, yet preclinical or early clinical studies suggest potential activity in pediatric cancer (Figure 1 , Pathway #2). For example, the IGF1 signaling pathway seems to be a significant axis for targeting Ewing's sarcoma, with an overall 10–15% objective response rate as a single agent in patients with refractory disease (Patel et al, 2009 ). While it is unclear if this response rate as a single agent is sufficient for FDA approval, multiagent therapies could be effective.…”
mentioning
confidence: 99%